Clinical and cost effectiveness of enhanced oral healthcare in stroke care settings (SOCLE II): A pilot, stepped wedge, cluster randomized, controlled trial protocol. Issue 6 (16th June 2015) - Brady, Marian C.; Stott, David; Weir, Christopher J.; Chalmers, Campbell; Sweeney, Petrina; Donaldson, Cam; Barr, John; Barr, Marion; Pollock, Alex; McGowan, Sheena; Bowers, Naomi; Langhorne, Peter
<x xml:space="preserve">Abstract</x> Rationale Stroke‐associated pneumonia, a leading cause of hospital‐acquired infection after stroke, affects a fifth of stroke survivors annually. Associated with increased risk of death and poorer rehabilitation outcomes, research suggests a possible relationship between stroke‐associated pneumonia and patients' oral health. Aim The aim of this study is to evaluate the feasibility of a randomized controlled trial of the clinical and cost effectiveness of enhanced oral healthcare vs. usual oral healthcare for people in stroke care settings. Design Our pilot, multicentered, pragmatic, stepped wedge, cluster randomized controlled trial oral healthcare [Stroke Oral healthCare pLan Evaluation (SOCLE II)] will compare enhanced oral healthcare intervention and usual oral healthcare. Over 13 months, across 4 wards, we seek to recruit 400 patients (estimating an average of 23 beds per site and a 50% recruitment rate) and 60 nursing staff (estimating an average of 20 members of staff per site and a 75% recruitment rate). Initially, control data (usual oral healthcare) will be collected from all sites. In a randomized, stepped manner, wards will convert to deliver the enhanced oral healthcare intervention. Study outcome(s) Outcomes will be captured across dimensions of care (as recommended for evaluations of complex interventions) at baseline and weekly thereafter. Primary outcomes are pneumonia (patients), knowledge and attitudes (staff), and specialist dental referrals (service). Secondary outcomes include oral health quality of life, plaque, antibiotics, length of stay, death (patients), use of oral healthcare equipment and products, completed assessments, and documented oral healthcare plans (staff). Discussion As one of the first stepped wedge, cluster randomized, controlled trials in stroke care mapping of the complex intervention, our choice of primary and secondary outcomes and choice of trial design are described.